If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.04 + 0.01(60) = 0.04(X + 60) Multiply 0.01 * 60 0.04 + 0.6 = 0.04(X + 60) Combine like terms: 0.04 + 0.6 = 0.64 0.64 = 0.04(X + 60) Reorder the terms: 0.64 = 0.04(60 + X) 0.64 = (60 * 0.04 + X * 0.04) 0.64 = (2.4 + 0.04X) Solving 0.64 = 2.4 + 0.04X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-0.04X' to each side of the equation. 0.64 + -0.04X = 2.4 + 0.04X + -0.04X Combine like terms: 0.04X + -0.04X = 0.00 0.64 + -0.04X = 2.4 + 0.00 0.64 + -0.04X = 2.4 Add '-0.64' to each side of the equation. 0.64 + -0.64 + -0.04X = 2.4 + -0.64 Combine like terms: 0.64 + -0.64 = 0.00 0.00 + -0.04X = 2.4 + -0.64 -0.04X = 2.4 + -0.64 Combine like terms: 2.4 + -0.64 = 1.76 -0.04X = 1.76 Divide each side by '-0.04'. X = -44 Simplifying X = -44
| 2x+y=352y+x+11÷7=10 | | (9)(-9)/2 | | -14y-11=6y+19 | | (2x)+(x-20)+(x/3)=180 | | 56s^2-17s-3=0 | | 14-45=3(x-1)-4 | | 4b+2=-18 | | s^2-4st+4t^2=0 | | 14-11=x-6 | | x/46=-3 | | 6x+176=15x-13 | | (2)(-2)/2 | | (-4x^8y^2)(13y^3)(0)= | | 1/2(10x-7)=3 | | 6t^2+20t-16=0 | | M+5=2m-11 | | -3(6n-4)+4n= | | 7x+63=-21 | | 165-3x=33x+17 | | -12a^2+26a+56=0 | | (0+0)/2 | | (0+10)/2 | | 0+10/2 | | y=40+5 | | (4w+7)(2w-9)=0 | | 5n+4=2n+27 | | 56v^2+23v-63=0 | | 3X+10=6X+40 | | 5x+5X=-67-7x | | -7(x-6)= | | 3.75/0.4 | | 18+10y=4y-6 |